Aplikasi Shringking Core Model (SCM) Pada Reaksi Deasetilasi Kitin Menjadi Kitosan - Mochamad Reizal Ath Thariq; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chitosan is derived from chitin compound used in the biomedical field. Chitosan can be synthesized from ebi waste.Chitosan can be produced by chemichal methods through the deproteinasi process, the demineralization process and the deacetylation process.in this research, Ebi powder was reacting with NaOH 3.5% (deproteinasi), ratio 1:10 (w/v) for 2 hours stirring by 150 rpm. The product reacted with HCl 1 N (demineralization), ratio 1:15 (w/v) for 1 hour stirring by 150 rpm. Then product was reacting using NaOH 50% (deacetylation), ratio 1:20 (w/v) at a temperature of 100oC, 110oC and 120oC with stirring by 150 rpm for 2 hours. Samples were taken every 10 minutes rise as much as 10 mL, washed until pH neutral and dried. Deacetylation degree of chitosan analyzed using acid-base titration method. The highest degree of deacetylation of the chitosan will be 71.68% to 80.28% at a temperature of 100-120oC. The best reaction kinetics model to describe the occur in the synthesis of chitosan is a model of ash layer (chitosan) to control.Keywords: deacetylation, reaction kinetics, chitosan, waste ebi, shrinking, core model.